Bis(alkyl) rare-earth complexes coordinated by bulky tridentate amidinate ligands bearing pendant Ph2PO and Ph2PNR groups. Synthesis, structures and catalytic activity in stereospecific isoprene polymerization. Issue 46 (7th November 2016) - Rad'kova, Natalia Yu.; Tolpygin, Aleksei O.; Rad'kov, Vasily Yu.; Khamaletdinova, Nadia M.; Cherkasov, Anton V.; Fukin, Georgi K.; Trifonov, Alexander A.
Abstract : Replacement of Ph2 PO group by Ph2 PNPh leads to a switch of stereoselectivity from cis -1, 4 to trans -1, 4. Abstract : A series of new tridentate amidines 2-[Ph2 PX]C6 H4 NHC( t Bu)N(2, 6-R2 C6 H3 ) (X = O, R = iPr (1 ); X = S, R = Me (2 ); X = NPh, R = Me (3 ); X = N(2, 6-Me2 C6 H3 ), R = Me (4 )) bearing various types of donor Ph2 PX groups in a pendant chain was synthesized. Bis(alkyl) complexes {2-[Ph2 PX]C6 H4 NC( t Bu)N(2, 6-R2 C6 H3 )}Ln(CH2 SiMe3 )2 (Ln = Y, X = O, R = iPr (5 ); Ln = Er, X = O, R = iPr (6 ); Ln = Lu, X = O, R = iPr (7 ); Ln = Y, X = NPh, R = Me (8 ); Ln = Lu, X = NPh, R = Me (9 ); Ln = Lu, X = N(2, 6-Me2 C6 H3 ), R = Me (10 )) were prepared using alkane elimination reactions of1, 3 and4 with Ln(CH2 SiMe3 )3 (THF)2 (Ln = Y, Er, Lu) in toluene and were isolated in 45 (5 ), 62 (6 ), 56 (7 ), 65 (8 ), 60 (9 ), and 60 (10 ) % yields respectively. The X-ray diffraction studies showed that complexes6–8 are solvent free and feature intramolecular coordination of the PX (X = O, NPh) group to the lanthanide ions. The ternary systems5–10 /borate/AlR3 (borate = [PhNHMe2 ][B(C6 F5 )4 ], [Ph3 C][B(C6 F5 )4 ], AlR3 = AliBu3, AliBu2 H; molar ratio = 1/1/10 or 1/1/1, toluene) proved to be active in isoprene polymerization and enable complete conversion of 1000–10 000 equivalents of the monomer into a polymer at 25 °C within 0.5–24 h affording polyisoprenes with polydispersities M w / M n = 1.22–3.18. A comparative study of the catalytic performance of the bis(alkyl) complexes coordinated by tridentate amidinate ligands containing different pendant donor groups demonstrated that replacement of the Ph2 PO group by Ph2 PNPh leads to a switch of stereoselectivity in isoprene polymerization from cis -1, 4 (up to 98.5%) to trans -1, 4 (up to 84.8%). And conversely introduction of methyl substituents in the 2, 6 positions of the phenyl group of the Ph2 PNPh fragment allows us to restore the 1, 4- cis stereoselectivity of the catalytic systems based on bis(alkyl) complex10 (up to 86.4%).